HUBUNGAN TINGKAT PENDIDIKAN PENDIDIK DENGAN KOMUNIKASI DALAM PEMBELAJARAN DI TK SE-KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU - Wiwit, Oktisar; Risma, Devi; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: the study aimes to identifying how the level of teachers’ education and the communication on learning in the kindergarten of ujung batu in rokan hulu district. This study using the population of all of the teachers in kindergarter of ujung batu in rokan hulu district, the number of 40 people. This study used the sample of saturated. It means all of the population as a sample techniques of collecting data used is questionnaires. Techniques of data analysis using a technique konferensial and analysis, correlation chi square. The results of this study showed that, there is no connection between the levels of teachers’ education and the communication on learning. This is in view of Chihitung < Chitable or 16.41% < 40.113%.Keywords: level of teachers’ education, communication on learning